1990
DOI: 10.1093/carcin/11.3.451
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase and glutathione peroxidase expression in normal and tumour human tissues

Abstract: Glutathione S-transferases play a central role in drug detoxification and have been implicated in the sensitivity of tumour cells to anticancer drugs. In this study, glutathione S-transferase (GST) isozyme expression in normal and tumour tissue from human lung, colon, stomach, breast, kidney and liver tissue has been quantified using sensitive and subunit specific radioimmunoassays (RIA), together with Western blot analysis and measurement of substrate metabolism. Glutathione S-transferase pi was the predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
108
1
6

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(124 citation statements)
references
References 0 publications
9
108
1
6
Order By: Relevance
“…The present study of a large number of patients has demonstrated loss of GST P expression in DCIS when compared with normal breast epithelium. These results differ from those in other epithelia in which GST P expression is increased in dysplasia and in carcinoma compared with normal cells (Sato, 1989;Howie et al, 1990). …”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The present study of a large number of patients has demonstrated loss of GST P expression in DCIS when compared with normal breast epithelium. These results differ from those in other epithelia in which GST P expression is increased in dysplasia and in carcinoma compared with normal cells (Sato, 1989;Howie et al, 1990). …”
Section: Discussioncontrasting
confidence: 94%
“…cervical viral warts (Carder et al, 1990). A wide variety of invasive carcinomas show increased GSTP expression (Howie et al, 1990), although this is not a universal phenomenon (Harrison, 1993).GST P is the major GST class in breast cancers and it is overexpressed in a subclass of oestrogen receptor-poor carcinomas (Howie et al, 1989). The implications for therapy are highlighted by data from a breast carcinoma cell line showing that increased GST expression and loss of oestrogen receptors occurs during acquisition of a multidrug-resistant phenotype (Moscow et al, 1988;Vickers et al, 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The GSTs comprise at least five gene families represented by the four cytosolic classes, Alpha, Mu, Theta and Pi, and at least one distinct membrane-associated microsomal class (Morgenstern et al, 1990). The distribution of GST isoenzymes in human tissues is not uniform and altered expression of GSTs has been demonstrated in a variety of tumour tissues (Howie et al, 1990). GST Pi acts as a marker of preneoplasia in animal models (Sato et al, 1987) and has been implicated in the acquisition of a drug resistant phenotype during carcinogenesis (Batist et al, 1986).…”
mentioning
confidence: 99%
“…Regarding GSH-dependent ∆ 5 -∆ 4 isomerase activity of this class of enzyme, it has been shown that steroidogenic factor 1 (SF-1) is involved in regulation of expression of GSTA genes (Matsumura et al, 2013). Aberrant overexpression has been observed in various malignancies such as colorectal (Hengstler et al, 1998) and lung cancer (Carmichael et al, 1988), while decrease in alpha class GSTs has been observed in stomach and liver tumors (Howie et al, 1990). A detailed recent review on GSTA1 can be found in Wu and Dong, 2012.…”
Section: Expressionmentioning
confidence: 99%